MUSEUMS IN MEMORY OF VICTIMS OF REPRESSION: WORLD EXPERIENCE AND PROSPECTS FOR THE CREATION OF A NATIONAL MUSEUM IN UZBEKISTAN (World Bulletin of Social Sciences, 2024)
This article analyzes the importance of creating a museum in memory of victims of repression in Uzbekistan, based on the study of the world experience of similar institutions. The paper examines examples of leading museums such as the Holocaust Museum in Washington, the Yad Vashem Memorial in Israel, and the ALGIERS Museum in Kazakhstan. Special attention is paid to their role in preserving historical memory, educational activities, and the formation of civic responsibility. The article highlights the importance of using modern technologies 1993 historical data. Prospects for the integration of archival materials and the creation of a national database on victims of repression are also being analyzed, which will ensure wide availability of knowledge and strengthen the link between generations. The study confirms that the creation of a museum in memory of the victims of repression in Uzbekistan will be an important step in preserving national identity, restoring historical justice and preventing the recurrence of such tragedies. This will not only preserve the memory of the tragic events of the past, but also become a platform for educating an informed and responsible society.